Representation of Local Wisdom in the Dumia Umbanua Traditional Ceremony in Laikit Village (British Journal of Multidisciplinary and Advanced Studies, 2023)
The Dumia Umbanua traditional ceremony is an annual ceremony that is held to clean or remodel an existing village. Local wisdom contained in the Dumia Umbanua traditional ceremony can be seen from the purpose of this study, namely to describe the form, function for the supporting community, and the meaning contained in the ceremonial equipment. The method used is a qualitative descriptive method with semiotic analysis. The results showed that the form of the Dumia Umbanua traditional ceremony was in the form of gratitude and as a form of entertainment. The function of the Dumia Umbanua traditional ceremony is the inheritance of social norms, social integrity, cultural preservation, and entertainment. The meaning of verbal symbols in the Dumia Umbanua traditional ceremony is contained in the expression when the ceremony procession is carried out and the meaning of non-verbal symbols is contained in ceremonial equipment such as pork hearts, offerings, yellow coconut leaves, dotu water, and tawaang.